2016
DOI: 10.14740/cr477w
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Intervention of a Persistent Left Superior Vena Cava Draining Into Left Pulmonary Vein and Coarctation of the Aorta

Abstract: We describe a 54-year-old male with history of type II DM, hypertension and dyslipidemia during admission for bronchopneumonia discovered to have coarctation of the aorta and a persistent left superior vena cava (PLSVC) draining into the left atrium through the left superior pulmonary vein. The latter was thought to contribute to a transient ischemic attack and an episode of chest pain resulting in ST-segment elevation in the inferior leads. He was treated with coarctation stenting and percutaneous exclusion o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…As with the general expert consensus that led to prior guidelines for comparable shunt lesions such as unroofed coronary sinus ( 8 ), closure of an LSVC with a left-sided heart connection is reasonable: significant hemodynamic shunt (pulmonary-to-systemic flow ratio >1.5), exertional hypoxia, or embolic events. The transcatheter closure technique of the LSVC with the use of vascular plug is similar to what is described in published reports ( 7 , 9 ). However, the more proximal location of the LSVC and LUPV confluence in this patient did require careful deployment of the plug, to avoid jeopardizing LUPV drainage.…”
Section: Discussionmentioning
confidence: 76%
“…As with the general expert consensus that led to prior guidelines for comparable shunt lesions such as unroofed coronary sinus ( 8 ), closure of an LSVC with a left-sided heart connection is reasonable: significant hemodynamic shunt (pulmonary-to-systemic flow ratio >1.5), exertional hypoxia, or embolic events. The transcatheter closure technique of the LSVC with the use of vascular plug is similar to what is described in published reports ( 7 , 9 ). However, the more proximal location of the LSVC and LUPV confluence in this patient did require careful deployment of the plug, to avoid jeopardizing LUPV drainage.…”
Section: Discussionmentioning
confidence: 76%
“…The unique anatomic variant in our patient was amenable to re-routing and preservation of LSVC return to the RA by transcatheter placement of a covered stent; without sacrificing the systemic venous pathway by device occlusion of the LSVC in previous reports. 4 , 7 , 8 , 10 , 12 This strategy also avoids the risks of a re-do sternotomy, cardiopulmonary bypass, and attendant surgical morbidities. This concept is similar to the recently reported covered stent correction of sinus venosus atrial septal defect with encouraging early outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Although these are usually without significant clinical implications, awareness of these anomalies is necessary to avoid diagnostic pitfalls and is an essential pre-operatively or pre-transcatheter intervention [4]. Few studies suggested a correlation between venae cavae anomalies and CoA, such as persistent left-sided SVC and CoA [5]. There is a reported case of interrupted left-sided IVC with hemiazygous continuation to persistent left-sided SVC in a patient with CoA [6].…”
Section: Introductionmentioning
confidence: 99%